Trade in environmental goods, with focus on climate-friendly goods and technologies - ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2011)
Paragraph 31(iii) of the Doha Ministerial Declaration mandates to the liberalization of environmental goods and services. This mandate offers a good opportunity to put climate-friendly goods and services on a fast track to liberalization. Agreement on this paragraph should represent one immediate contribution that the WTO can make to fight against climate change. This paper presents the key issues surrounding the liberalization of trade in climate-friendly goods and technologies in WTO environmental goods negotiations. It begins with discussing what products to liberalize and how. Given that WTO Members are divided by this key issue, the paper explores options to move current negotiations on the liberalization of trade in environmental goods and technologies forward, both within and outside the WTO. Recognizing that there is no one-size-fits-all strategy for tariff liberalization for all countries and for all environmental goods, the paper suggests the need for a high degree of flexibility to accommodate different situations and stakes in the liberalization of trade in environmental goods. Given that there are simply not enough environmental markets or these markets are weak in many developing countries, the paper emphasizes that creating markets for environmental goods in developing countries is far more important than just improving market-access conditions for associated goods, and discusses how to best serve the interests and concerns of developing countries.
Keywords: F18; F13; P28; Q42; Q48; Q56; Q54; Q58; Q48; 330; Environmental Goods and Services; Low-Carbon Goods and Technologies; Market Access; Doha Round; WTO; Renewable Energy Technologies